Thank You to Our 2021 Reviewers. Issue 4 (24th April 2022) - Destouni, Georgia; Bierkens, Marc F. P.; Hall, Jim; Islam, Shafiqul; Jha, Madan Kumar; Kollet, Stefan; Luce, Charles H.; Mackay, D. Scott; Moradkhani, Hamid; Sanchez‐Vila, Xavier; Singha, Kamini; Stahl, Kerstin; et al.
Abstract : On behalf of the editorial board of Water Resources Research (WRR) and the entire water science community, we want to express our most heartfelt gratitude to all who reviewed manuscripts for the journal in 2021. Your great efforts have ensured and improved the high quality and impact of the WRR papers and generally of research in our field. In 2021, the 2, 960 individuals listed below have contributed 4, 788 peer reviews with the 432 people indicated in italics, reviewing three or more papers for the journal. The editors, associate editors, and authors of WRR sincerely thank all our reviewers and look forward to the exciting advances that will be published in WRR in 2022.